INTEGRATED CURRICULUM DEVELOPMENT OF LOCAL CONTENT AND ISLAMIC VALUES AT RAUDHATUL ATHFAL AR RAFIF YOGYAKARTA - Mushlih, Ahmad (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2022)
The value of local content is an important aspect that needs to be familiarized from an early age as a core value in community life skills. However, there are still certain local content values that have not been integrated in the management of the ECCE curriculum. The research method uses descriptive qualitative with data collection using interviews, observations and documentation. Meanwhile, the data validity test uses technical triangulation with analysis using data reduction, data supply and verification. The results showed that RA AR Rafif has developed a curriculum of local content and the value of morality integrated into local cultural and Islamic activities which are packaged in the peak activities of themes and habituation, the appropriateness of learning activities. Curriculum development is documented in the curriculum at the unit level of education RA AR Rafif in documents I and II which contain the vision and mission, annual programs, semesters, weekly and daily. In addition, development includes the development of indicators of developmental achievement for early childhood against the output of local content values and Islamic values.